2016
DOI: 10.1111/raq.12185
|View full text |Cite
|
Sign up to set email alerts
|

Overview of 3 year precommercial seafarming of Macrocystis pyrifera along the Chilean coast

Abstract: Chile is one of the main producers of seaweeds in the world; however, most of the production comes from harvesting natural beds and only 2.4% from cultures, dominated by the agarophyte Gracilaria chilensis. One of the most exploited resources is the giant kelp Macrocystis pyrifera, which is sold fresh for abalone feed and dry for alginate extraction. Recently, new possible markets are developing for this species, for example human consumption and biofuel/chemical production that could increase the demand and j… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
39
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 50 publications
(49 citation statements)
references
References 64 publications
2
39
1
Order By: Relevance
“…Our results elucidate the photoacclimation mechanisms that can allow farming Macrocystis pyrifera in relatively shallow waters (Camus et al. , ). Shallow water cultivation reduces the challenges of installing, monitoring, and harvesting of final biomass in deeper waters (Altamirano ).…”
Section: Discussionsupporting
confidence: 60%
“…Our results elucidate the photoacclimation mechanisms that can allow farming Macrocystis pyrifera in relatively shallow waters (Camus et al. , ). Shallow water cultivation reduces the challenges of installing, monitoring, and harvesting of final biomass in deeper waters (Altamirano ).…”
Section: Discussionsupporting
confidence: 60%
“…On a global scale, most offshore seaweed biomass is produced in Indonesia, the Philippines, China, India, and Tanzania, and is currently under investigation in US and EU biomass programs . The concepts of offshore marine biomass cultivation include farms for kelp growth, tidal flat farms, floating seaweed cultivation settings, ring cultivation systems, and, most recently, wind‐farm integrated systems and underwater ropes …”
Section: Introductionmentioning
confidence: 99%
“…Pilot-production has demonstrated that 124 wet ton.ha -1 of M. pyrifera can be achieved using wild individuals to seed ropes for suspended systems [32]. The development of M. pyrifera aquafarming is expected to emerge rapidly for several reasons: established procedures for cultivation in hatcheries [33] and open ocean [32] allow for the testing of the agronomic performance of a large array of genotypes and pilot scale production; technology used to convert biomass to bioethanol implemented at the pilot scale [34,35]; and identification of novel components for food and pharmaceutical uses that add value to the biomass production [5,36,37]. M. pyrifera is considered to be a highly plastic species [38,39], yet some morphological traits were considered to express a strong phylogenetic signal.…”
Section: Introductionmentioning
confidence: 99%